Vibration Analysis of Smart Beam (International Journal of Engineering and Computer Science, 2017)
These instructions Vibration of a smart beam is being controlled by using opposite directional force to the structure. Now a day’s active vibration control is frequently being used in aircraft, submarine, automobile, helicopter blade, naval vessel. In this a smart plate with one pair of piezoelectric lamination is used to study the active vibration control. The smart plate consists of rectangular aluminium beam modelled in cantilever configuration with surface bonded piezoelectric patches. In this case, disturbance is produced using exciter. The piezoelectric sensors are used to detect the vibration. Simultaneously, feedback controller sends correction information to the actuator that minimizes the vibration. The study uses ANSYS-11 software to derive the finite element model of the smart plate. Based on this model, the optimal sensor locations are found and actual smart beam is produced. In this experiment a suitable control methodology is find by which the controller gain optimizes to get more effective vibration control with minimum control input.